The Impact of Scandalous News in the Automobile Manufacture on Companies from the Same Industry: A Comparative Study on the Chinese and European Markets - Mews, Anastasia (European Scientific Journal, ESJ, 2021)
This paper examines the effect of scandalous news on corporate reputation of rival firms from the same industry and investigates the effects’ differences in China and in Europe, providing evidence that scandalous news influences not only the target company itself, but also other companies from the industry. For this purpose, the paper uses the 2015 Volkswagen emissions scandal as a natural experiment. Volkswagen, BMW, Mercedes-Benz, Audi and Porsche were selected as sample companies. To measure reputational spillover effects, cumulative abnormal stock returns and sales growth of the sample companies are calculated and compared before and after the announcement of the scandal. The methodology adopted for estimating stock returns is the event study method, which measures the impact of a specific event on the value of a firm. Stock price data is collected from Bloomberg and used to calculate cumulative abnormal returns of the sample companies. Furthermore, difference-in-differences estimation is used to compare the sample companies’ sales growth before and after the scandal. Volkswagen, Audi, BMW and Mercedes-Benz are included in the treatment group, whereas 29 non-German car manufacturers were selected as the control group. The results show that overall rival companies were affected by the scandal, cumulative abnormal returns declined by 6% and 10% for BMW and Mercedes-Benz respectively, showing the contagion effect. However, the sales growths of these two manufacturers greatly increased, specifically on the Chinese market for Mercedes-Benz and on the European market for BMW, proving dominance of the competitive effect and differences of the reputational spillover effects across countries.